Erosion, permeation and outgassing performances of tin coating under/after hydrogen plasma iffadiation - Glazunov, G.P.; Volkov, E.D.; Veremeyenko, V.P.; Kosik, N.A.; Kutsyn, Al.A.; Langner, J.; Langner, E.; Mironov, Yu.K.; Nazarov, N.I.; Piekoszewski, J.; Sadowski, M.; Stanislawski, J.; et al. (Вопросы атомной науки и техники, 2000)
An erosion behavior of TiN-coated stainless-steel (SS) surfaces was investigated during biased-limiter experiments within the Uragan-3M torsatron and during simulation experiments, which were performed with plasma-accelerator and glow-discharge (GD) plasmas. For a TiN-coated SS head-plate of a limiter the arc ignition probability was found to be lower than 10-4 per plasma pulse. Possible physical mechanisms of this effect had been discussed. Within special vacuum stands, using thermal-desorption and mass-spectrometry methods, there were performed measurements of an outgassing rate and hydrogen permeability of TiNcoatings. The negligible outgassing from TiN-coated SS samples, during their heating up to 473 K, was observed after a cleaning procedure with a molecular hydrogen inflow under pressure of about 10-4 Torr, on contrary to the considerable increase of (q) rate for the irradiated samples. Measured values of the TiN-film hydrogen permeability were several times lower, and activation energy of the hydrogen permeation was considerably lower than that for the SS films (15 kJ/mole instead of 19.9 kJ/mole). The use of TiN-coated SS and diffusion membranes, for the reduction of the erosion, recycling, and hydrogen isotope inventory control, as well as for improvement of vacuum conditions, has been considered.